Pasar Tradisional Sei Guntung Di Kabupaten Indragiri Hilir Dengan Pendekatan Arsitektur Tepian Air - Muhammad Mansyur; Wahyu Hidayat; Mira Dharma Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Sei Guntung Traditional Market is a market in the form of wooden tents selling on Yos Sudarso road in the form of dams and also on the banks of the Kateman River. This resulted in the road becoming narrow and the occurrence of congestion and pollution of the river due to the actions of the traders. Therefore, a new container for merchants is needed that is neatly and cleanly arranged. This development also pays attention to the standards of market health requirements and the dominant aspects of waterfront architecture and its elements. The design method used is the results of field surveys, documentation, analysis of qualitative data and quantitative data. The results of this design apply the concept of pompong analogy. The shape of the building in the form of pompong is the result of the application of pompong elements and waterfront architectural themes. This design utilizes the potential of the river as a river transportation service, sitting park, and foodstall. This design will later function as an area of sale and purchase with recreational facilities and public open space for the Kateman community.Keywords: Kateman, Sei Guntung, Traditional Market, Waterfront Architecture, Pompong.